Hubungan Antara Status Gizi Dengan Perkembangan Motorik Kasar Pada Balita - Arisda Candra Satriawati; Sitti Sarti (IJMT : Indonesian Journal of Midwifery Today, 2021)
Healthy toddlers (1-3 years old) will experience reasonable and normal development, according to the ability standards of children their age, while children with impaired nutritional status will experience obstacles in their development. This study aims to study the relationship nutritional status and gross motor development of toddler in ujung piring Village, Bangkalan Regency.The research method based on Cross Sectional where the population is all children aged 1-3 years as many as 80 children, while the sample taken is 45 people by simple random sampling. The data collection method used the standard deviation table and KPSP, with a cross tabulation table and tested with the Spearman rank test, with a significance level of = 0.05.The results of the study, most of the nutritional status of toddler is good nutrition (55.6%), most of the gross motor development of children is appropriate (64.4%). From the results of the Spearman rank test, a significance value of p = 0.000 (p<α) was obtained, which means that there is a relationshipnutritional status and children's gross motor development.The results of this study can be concluded that there is a relationship between nutritional status and gross motor development of children. For this reason, it is expected that parents will care more about their children, provide nutritious food and provide appropriate stimulation so that the growth and development of children can be exceeded in accordance with expectations.